Apocalypse of the alien god : Platonism and the exile of Sethian gnosticism - Burns, Dylan M. (Divinations : rereading late ancient religion, 2014)
Apocalypse of the Alien God shows that the fundamental break between the Platonic tradition and Judeo-Christianity began when the mystic Plotinus rejected the teachings of the Sethians, an influential group of Gnostics who operated at the intersection of Hellenic, Jewish, and Christian thought.